Moderasi Beragama dalam Kajian KH Said Aqil Siradj di Media Youtube - Widi, Widiya; Syahda Zahra, Alifarose; Ubaidillah, Ubaidillah (Prodi KPI FDPM IPMAFA Bekerjasama dengan Mafa Press IPMAFA Pati, 2023)
YouTube is a medium that has been successfully used as a place for preaching. One of them is KH Said Aqil Siradj's religious moderation preaching. The aim of this research is to analyze the use of content on NU Online You Tube with the figure KH Said Aqil Siradj because he is the Chairman of PBNU who is a leader in strengthening religious moderation. This research is a type of qualitative research using library or library research methods. This method can be used as a reference and grouping data such as books, articles and also information that supports this research. You Tube is the main source in this research which can be a reference for updates, a theoretical basis, and also additional references. The research results show that KH Said Aqil Siradj in his preaching on YouTube contains a message of religious moderation by prioritizing the pillars of harmony, non-violence and religious communities.